Nitrogen-Doped Carbon Nanosheets Decorated With Mn2O3 Nanoparticles for Excellent Oxygen Reduction Reaction - Qasim, Maryam; Hou, Jianhua; Qadeer, M. A.; Butt, Sajid; Farooq, M. Hassan; Farooq, M. Qasim; Idrees, Faryal; Tanveer, M.; Zou, Jijun; Tahir, Muhammad (Frontiers in Chemistry, 2019)
The purpose of this study is to develop an active, low cost, non-precious, stable, and high-performance catalyst for oxygen reduction reaction (ORR). In this regard, Mn2O3-decorated nitrogen-doped carbon nanosheets (Mn2O3/NC) are fabricated by a two-step strategy involving a hydrothermal method and a solid-state method. In the resultant structures, very fine Mn2O3 nanoparticles with an average size of about 5 nm are strongly attached to nitrogen-doped carbon nanosheets. The role of the Mn2O3 nanoparticles is to provide active sites for ORR, while the presence of the nitrogen-doped carbon not only enhances the conductivity of the overall structure but is also helpful for overall stability. The Mn2O3/NC shows good onset potential (0.80 V@−1 mA/cm2), methanol crossover effect, and stability (90%).